The Adoption of QR Code Mobile Payment Technology During COVID-19: A Social Learning Perspective - Tu, Ming; Wu, Lei; Wan, Hua; Ding, Zhoujin; Guo, Zizheng; Chen, Jiayi (Frontiers in Psychology, 2022)
The increasing number of quick response (QR) code mobile payment users heralds the coming of a cashless society. However, the extent to which the coronavirus disease 2019 (COVID-19) pandemic accelerated the adoption of QR code mobile payment has not been sufficiently researched. Based on social learning theory, this study models how external interaction with the environment has affected the internal appraisal and behavioral intention to adopt QR code mobile payment during COVID-19. Empirical results from 248 respondents revealed that perceived severity and social influence positively affected the perception of utilitarian and health benefits of respondents, which in turn influenced the behavioral intention to use the QR code mobile payment. The theoretical contribution and managerial implications of this study are also discussed.